Effect of acetyl L-carnitine on human retinal pigment epithelium-19 cells in hypoxic conditions - Ali, Dal; Onur, Çatak; Murat, Erda?; Mehmet, Canleblebici; Ebru, Önalan; Ilay, Buran (International Journal of Ophthalmology (c/o Editorial Office), 2024)
•AIM: To investigate the effect of acetyl - L - carnitine (ALCAR) on cell viability, morphological integrity, and vascular endothelial growth factor (VEGF) expression in human retinal pigment epithelium (ARPE- 19) cells using a hypoxic model. •METHODS: In the first set of experiments, the optimal CoCl2 dose was determined by exposing ARPE - 19 cell cultures to different concentrations. To evaluate the effect of ALCAR on cell viability, five groups of ARPE - 19 cell culture were established that included a control group, a sham group (200 ? M CoCl2), and groups that received 1, 10 and 100 mM doses of ALCAR combined with 200 ? M CoCl2, respectively. The cell viability was measured by MTT assay. The morphological characteristics of cells were observed by an inverted phase contrast microscope. The levels of VEGF and HIF-1? secretion by ARPE-19 cells were detected by enzyme linked immunosorbent assay (ELISA) assay. • RESULTS: ARPE - 19 cells were exposed to different doses of CoCl2 in order to create a hypoxia model. Nevertheless, when exposed to a concentration of 200 ? M CoCl2, a notable decrease in viability to 83% was noted. ALCAR was found to increase the cell viability at 1 mM and 10 mM concentrations, while the highest concentration (100 mM) did not have an added effect. The cell viability was found to be significantly higher in the groups treated with a concentration of 1 mM and 10 mM ALCAR compared to the Sham group (P = 0.041, P = 0.019, respectively) . The cell viability and morphology remained unaffected by the greatest dose of ALCAR (100 mM) . The administration of 10 mM ALCAR demonstrated a statistically significant reduction in the levels of VEGF and HIF - 1? compared with the Sham group (P = 0.013, P = 0.033, respectively) . • CONCLUSION: The findings from the current study indicate that ALCAR could represent a viable therapeutic option with the potential to open up novel treatment pathways for retinal diseases, particular relevance for age- related macular degeneration (AMD) . However, to fully elucidate ALCAR ' s application potential in retinal diseases, additional investigation is necessary to clearly define the exact mechanisms involved. © 2024 International Journal of Ophthalmology (c/o Editorial Office). All rights reserved.
?????????????????????-19 ?????
Keywords: acetyl-L-carnitine (ALCAR); human retinal pigment epithelium (ARPE - 19); hypoxia - inducible factor 1 (HIF-1?); vascular endothelial growth factor (VEGF)